2009
DOI: 10.1242/jeb.035196
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory and cardiovascular actions of centrally and peripherally administered trout pituitary adenylate cyclase-activating polypeptide (PACAP) and vasoactive intestinal peptide (VIP) in the unanaesthetized trout

Abstract: SUMMARY V TOT ). However, the maximum hyperventilatory effect of PACAP was approximately 2.5-fold higher than the effect of VIP at the 100pmol dose (PACAP, V TOT +5407±921arbitrary units, a.u.; VIP, V TOT +2056±874a.u.; means ± s.e.m.). When injected centrally, only PACAP produced a significant increase in mean dorsal aortic blood pressure (P DA ) (100pmol: +21%) but neither peptide affected heart rate (f H ). Intra-arterial injections of either PACAP or VIP were without effect on the ventilatory variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Previous studies found that intrathecal VIP, administered at the spinal level of T2, did not affect MAP in the rat (Lai et al ., 1997), and that intracerebroventricular VIP did not affect MAP or HR in the trout (Le Mevel et al ., 2009). Apart from the differences in sites of VIP administration and species, the much lower doses used in these earlier studies may account for the lack of observed MAP and HR responses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that intrathecal VIP, administered at the spinal level of T2, did not affect MAP in the rat (Lai et al ., 1997), and that intracerebroventricular VIP did not affect MAP or HR in the trout (Le Mevel et al ., 2009). Apart from the differences in sites of VIP administration and species, the much lower doses used in these earlier studies may account for the lack of observed MAP and HR responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the goldfish, peripheral PACAP reduces food intake (Matsuda et al, 2006). We also demonstrated that trout PACAP-27 and trout VIP act on the CNS to increase ventilation (Le Mével et al, 2009b) and to reduce the cardiac BRS (Lancien et al, 2011). …”
Section: Effects Of Intracerebroventricular Injections Of Neuropeptidesmentioning
confidence: 82%
“…The most pronounced action of PACAP is evoking hyperventilation through an increase in VA rather than VF. For instance, after 50 and 100 pmol PACAP this maximal change in VA, expressed as a percentage of the pre-injection value, reaches about 100 and 200%, respectively, while the elevation of VF is only about 10 and 35% (Le Mével et al, 2009b). …”
Section: Effects Of Intracerebroventricular Injections Of Neuropeptidesmentioning
confidence: 99%